Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.33480/pilar.v15i1.103
|View full text |Cite
|
Sign up to set email alerts
|

Perancangan Sistem Informasi Booking Perekaman E-KTP (Si Mbok) Berbasis Web

Abstract: A based information system is a system that can be used for the dissemination of information through internet services. In this case, the internet is becoming the provider of a set of information that is posted or uploaded, so that the public can see it every time. Therefore the presence of the internet makes it easier for people to be able to implement the results of the analysis of a system so that the formation of web-based information systems. Government services were supposed to use web-based infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 2 publications
0
5
0
10
Order By: Relevance
“…a. Observasi Observasi (Observation) merupakan teknik pengumpulan data dengan cara mengamati langsung objek penelitian dan menarik kesimpulan dari semua aktivitas objek tersebut (Sentosa, 2017). Sehingga semua informasi yang didapat bersifat akurat dan tepat (Basri et al, 2019). b. Wawancara Wawancara (Interview) adalah teknik penelitian yang menggunakan dialog langsung atau tidak langsung (tatap muka) atau melalui media tertentu antara pengunjung dan narasumber sebagai sumber data (Ahsanulkhaq, 2019).…”
Section: Pendahuluanunclassified
“…a. Observasi Observasi (Observation) merupakan teknik pengumpulan data dengan cara mengamati langsung objek penelitian dan menarik kesimpulan dari semua aktivitas objek tersebut (Sentosa, 2017). Sehingga semua informasi yang didapat bersifat akurat dan tepat (Basri et al, 2019). b. Wawancara Wawancara (Interview) adalah teknik penelitian yang menggunakan dialog langsung atau tidak langsung (tatap muka) atau melalui media tertentu antara pengunjung dan narasumber sebagai sumber data (Ahsanulkhaq, 2019).…”
Section: Pendahuluanunclassified
“…Information systems that have complexity, of course, have data storage (storage). Computerized database systems aim to maintain processed data or information and make the information available when needed (Basri, H., et al, 2019).…”
Section: Fig3 the Results Of A Survey Of Respondents About Saving On Blank Cardsmentioning
confidence: 99%
“…The elements of government, education, public and private industry, even UMKN have started to use information systems in carrying out their activities. An example of the use of the development of information systems in government is the existence of booking information system in the process of making website-based E-KTPs [1], in this study was found that the community eases of process of submitting E-KTPs [2]. In education field, information systems can be used as a desktop-based payment administration medium at SMAN I Cikampek [3], this study found the right solution in the payment administration process.…”
Section: Introductionmentioning
confidence: 88%